CON4EI: Bovine Corneal Opacity and Permeability (BCOP) test for hazard identification and labelling of eye irritating chemicals. (October 2017) - Verstraelen, Sandra; Maglennon, Gareth; Hollanders, Karen; Boonen, Francis; Adriaens, Els; Alépée, Nathalie; Drzewiecka, Agnieszka; Gruszka, Katarzyna; Kandarova, Helena; Willoughby, Jamin A.; Guest, Robert; Schofield, Jane; et al.
Abstract: Assessment of ocular irritation potential is an international regulatory requirement in the safety evaluation of industrial and consumer products. None in vitro ocular irritation assays are capable of fully categorizing chemicals as stand-alone. Therefore, the CEFIC-LRI-AIMT6-VITO CON4EI consortium assessed the reliability of eight in vitro test methods and computational models as well as established a tiered-testing strategy. One of the selected assays was Bovine Corneal Opacity and Permeability (BCOP). In this project, the same corneas were used for measurement of opacity using the OP-KIT, the Laser Light-Based Opacitometer (LLBO) and for histopathological analysis. The results show that the accuracy of the BCOP OP-KIT in identifying Cat 1 chemicals was 73.8% while the accuracy was 86.3% for No Cat chemicals. BCOP OP-KIT false negative results were often related to an in vivo classification driven by conjunctival effects only. For the BCOP LLBO, the accuracy in identifying Cat 1 chemicals was 74.4% versus 88.8% for No Cat chemicals. The BCOP LLBO seems very promising for the identification of No Cat liquids but less so for the identification of solids. Histopathology as an additional endpoint to the BCOP test method does not reduce the false negative rate substantially for in vivo Cat 1 chemicals. Highlights: Accuracy BCOP OP-KIT in identifying Cat 1 chemicals was 73.8%, No Cat was 86.3%. Accuracy BCOP LLBO in identifying Cat 1 chemicals was 74.4%, No Cat was 88.8%. BCOP LLBO very promising for identification of No Cat liquids but possibly less so for the identification of solids. Histopathology as additional endpoint to BCOP did not reduce the false negative rate substantially of in vivo Cat 1 chemicals.